Pengaruh Free Shipping, Discount dan Price Terhadap Minat Beli Konsumen Generasi Z Pada Platform Shopeefood Di Desa Sidodadi Kecamatan Biru - Biru - Rasyiddin, Rasyiddin; Salqaura, Siti Alhamra (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the effect of Free Shipping, Discounts, and Prices on Purchase Intention of Generation Z consumers on the Shopee Food platform in Sidodadi Village, Biru-Biru District. The study used a quantitative approach with a Generation Z population (born 1997-2021) totaling 1,223 people or 25.3% of the total 4,835 village residents. The sampling technique used the Slovin formula to obtain 93 respondents. Data were analyzed using SPSS with multiple linear regression analysis. The results showed that free shipping had a positive and significant effect on Purchase Intention with t-count (3.358) > t-table (1.986) and significance (0.001) < 0.05. Discounts had a positive and significant effect with t-count (3.189) > t-table (1.986) and significance (0.002) < 0.05. Price has a positive and significant effect with a calculated t-value (2.190) > t-value (1.986) and a significance level (0.031) < 0.05.Simultaneously, the third variable has a significant effect on Purchase Intention of Generation Z consumers on the Shopee Food platform in Sidodadi Village, Biru-Biru District with a calculated F-value (34.897) > F-value (2.706) and a significance level (0.000) < 0.05, indicating that Free Shipping, Discounts, and Price are important factors in increasing the purchase intention of Generation Z consumers.